2021
DOI: 10.3390/educsci11080427
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Students at Risk to Academic Dropout in Higher Education

Abstract: A main goal of the university institution should be to reduce the desertion of its students, in fact, the dropout rate constitutes a basic indicator in the accreditation processes of university centers. Thus, evaluating the cognitive functions and learning skills of students with an increased risk of academic failure can be useful for the adoption of strategies for preventing and reducing school dropout. In this research, cognitive functions and learning skills in 284 university students were evaluated. Academ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 43 publications
0
3
0
3
Order By: Relevance
“…En este sentido, si el éxito es escaso, el desempeño decae y la deserción se convierte en una opción. Asimismo, según lo señalado por Gómez et al (2021), los estudiantes con mayor riesgo de fracaso académico y, por consiguiente, de deserción, son aquellos que muestran un bajo nivel cognitivo y carecen de aptitudes para un aprendizaje eficaz.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…En este sentido, si el éxito es escaso, el desempeño decae y la deserción se convierte en una opción. Asimismo, según lo señalado por Gómez et al (2021), los estudiantes con mayor riesgo de fracaso académico y, por consiguiente, de deserción, son aquellos que muestran un bajo nivel cognitivo y carecen de aptitudes para un aprendizaje eficaz.…”
Section: Discussionunclassified
“…Los estudiantes con mayor riesgo de fracaso académico, y, por consiguiente, de deserción, son los que muestran bajo nivel cognitivo además de carecer de aptitudes para un aprendizaje eficaz (Gómez et al, 2021).…”
Section: Modelo Psicológicounclassified
See 1 more Smart Citation
“…Empirical studies [37][38][39] and an integrative review [39] considering higher education students from European, North, and South American contexts have similarly suggested that engagement in academic activities is positively linked to academic achievement and adjustment. On the other hand, students who participate less frequently in class and academic tasks tend to demonstrate a higher risk of dropout [40][41][42]. Thus, academic engagement is an important factor that prevents dropout and academic failure not only in high school [40] but also in higher education [6,42].…”
Section: Academic Engagementmentioning
confidence: 99%
“…Although we focused our analysis on work that applied machine learning and EDM techniques to predict student dropout, other techniques have been investigated for the detection and adoption of strategies for preventing and reducing student dropout. For instance, evaluating the cognitive functions and learning skills of students [34], using non-linear panel data models to analyze the determinants of student dropout [35], or applying learning analytics to identify students at risk of dropout [36].…”
Section: Related Workmentioning
confidence: 99%